2006
DOI: 10.1038/sj.jp.7211518
|View full text |Cite
|
Sign up to set email alerts
|

Oral sildenafil citrate lacks genotoxicity and cytotoxicity in a primate model: Callithrix jacchus

Abstract: Objective: To determine sildenafil citrate (SC) genotoxicity and cytotoxicity in the Callithrix jacchus.Study design: Fifteen organisms were assigned to one of three groups as follows: experimental (25 mg/kg of SC); negative control (glucose solution 5%); and positive control (3 mg/kg of cytocine arabinoside). Systemic hemodynamic changes were monitored in each animal before and after each treatment. A drop of blood was obtained before and after the treatment at 24-120 h. Smears were made and the frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
3
0
3
Order By: Relevance
“…Sildenafil citrate was previously tested by Snyder and Green (2001) and Lemus‐Varela et al (2006), but was detected neither mutagenic, nor carcinogenic.…”
Section: Discussionmentioning
confidence: 99%
“…Sildenafil citrate was previously tested by Snyder and Green (2001) and Lemus‐Varela et al (2006), but was detected neither mutagenic, nor carcinogenic.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that these effects are dose-dependent. There is experimental evidence that there are no genetic defects 26 and no neurodevelopmental impairment associated with its use. 6 In this study, as well as in the previous studies mentioned, 19,20 no systemic hypotension was observed.…”
Section: Discussionmentioning
confidence: 99%
“…También se ha comunicado la vasodilatación de la venas retinianas mayores 54 . En relación a la genotoxicidad y la citotoxicidad del sildenafilo, Lemus et al 55 recientemente han publicado un estudio que tranqui-Sola A y Baquero H. Sildenafilo oral en medicina neonatal liza, al demostrar en un modelo de primate, que este fármaco no produce este tipo de toxicidad.…”
Section: Efectos Adversosunclassified